The association between monocyte to high-density lipoprotein cholesterol ratio and chronic kidney disease in a Chinese adult population: a cross-sectional study - Lingling Xu; Dongling Li; Zongwei Song; Jin Liu; Yang Zhou; Junwei Yang; Ping Wen (Renal Failure)
Background Monocyte to high-density lipoprotein cholesterol ratio (MHR) was confirmed as a novel inflammatory marker and strongly associated with the risk of several diseases. This study aimed to investigate the relationship between MHR and chronic kidney disease (CKD) in a Chinese adult population.Methods In this cross-sectional study, 232,775 community-dwelling adults in Binhai who completed health checkups in 2021 were enrolled. Participants were categorized based on the MHR quartiles. Clinical characteristics of participants across different groups were compared using one-way ANOVA, Kruskal-Wallis h-test, and Chi-squared test as appropriate. Univariate and multivariable logistic regression analyses were taken to assess the relationship between MHR and the presence of CKD, as well as its association with low estimated glomerular filtration rate (eGFR) and proteinuria. Subgroup analyses were further executed to confirm the reliability of this relationship.Results A total of 21,014 (9.0%) individuals were diagnosed with CKD. Characteristic indicators including waist circumference, body mass index (BMI), blood pressure (BP), serum uric acid (SUA), triglyceride, and fasting blood glucose (FBG) showed a gradual increase with higher MHR quartiles, whereas parameters such as age, total cholesterol, high-density lipoprotein cholesterol (HDL-C), and eGFR decreased (p < .001). In the multivariable logistic regression analysis, we observed independent associations between MHR (per 1 SD increase) and CKD, as well as low eGFR and proteinuria, with odds ratio (ORs) and 95% confidence intervals (95%CIs) of 1.206 (1.186–1.225), 1.289 (1.260–1.319), and 1.150 (1.129–1.171), respectively (p < .001). Similar conclusions were confirmed in subgroup analysis stratified by gender, age, BMI, central obesity, hypertension, and diabetes mellitus, after justification for confounding factors.Conclusion Elevated MHR level was independently associated with the presence of CKD, suggesting that it might serve as a useful clinical tool for risk stratification, offering valuable insights to inform preventive and therapeutic approaches for clinicians in their routine medical practice.